Brassinosteroids Inhibit Autotropic Root Straightening by Modifying Filamentous-Actin Organization and Dynamics - de Bang, Louise; Paez-Garcia, Ana; Cannon, Ashley E.; Chin, Sabrina; Kolape, Jaydeep; Liao, Fuqi; Sparks, J. Alan; Jiang, Qingzhen; Blancaflor, Elison B. (Frontiers in Plant Science, 2020)
When positioned horizontally, roots grow down toward the direction of gravity. This phenomenon, called gravitropism, is influenced by most of the major plant hormones including brassinosteroids. Epi-brassinolide (eBL) was previously shown to enhance root gravitropism, a phenomenon similar to the response of roots exposed to the actin inhibitor, latrunculin B (LatB). This led us to hypothesize that eBL might enhance root gravitropism through its effects on filamentous-actin (F-actin). This hypothesis was tested by comparing gravitropic responses of maize (Zea mays) roots treated with eBL or LatB. LatB-and eBL- treated roots displayed similar enhanced downward growth compared with controls when vertical roots were oriented horizontally. Moreover, the effects of the two compounds on root growth directionality were more striking on a slowly-rotating two-dimensional (2-D) clinostat. Both compounds inhibited autotropism, a process in which the root straightened after the initial gravistimulus was withdrawn by clinorotation. Although eBL reduced F-actin density in chemically-fixed Z. mays roots, the impact was not as strong as that of LatB. Modification of F-actin organization after treatment with both compounds was also observed in living roots of barrel medic (Medicago truncatula) seedlings expressing genetically encoded F-actin reporters. Like in fixed Z. mays roots, eBL effects on F-actin in living M. truncatula roots were modest compared with those of LatB. Furthermore, live cell imaging revealed a decrease in global F-actin dynamics in hypocotyls of etiolated M. truncatula seedlings treated with eBL compared to controls. Collectively, our data indicate that eBL-and LatB-induced enhancement of root gravitropism can be explained by inhibited autotropic root straightening, and that eBL affects this process, in part, by modifying F-actin organization and dynamics.